2016
DOI: 10.15851/jap.v4n2.819
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivitas dan Spesifisitas Cystatin C dan Kreatinin Serum dalam Mendiagnosis Cedera Ginjal Akut pada Pasien Sepsis yang Dirawat di Ruang Rawat Intensif RSUP H. Adam Malik Medan

Abstract: AbstrakKreatinin serum memiliki banyak keterbatasan dalam mendiagnosis cedera ginjal akut (CGA) terutama dalam ruang lingkup unit perawatan intensif sehingga kurang sensitif untuk menggambarkan tingkat disfungsi ginjal pada pasien sakit kritis. Dari sekian banyak penanda biologis baru yang tersedia, terdapat 4 penanda biologis yang saat ini secara luas digunakan para klinisi di seluruh dunia untuk mendeteksi CGA, antara lain neutrophil gelatinase-associated lipocalin (NGAL), cystatin C, KIM-1, dan interleukin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
1
3
0
1
Order By: Relevance
“…Our study demonstrated that most of the COPD patients were heavy smokers, which are similar to results reported by other researchers in Adam Malik General Hospital (Medan) and M. Djamil Hospital (Padang), Indonesia [14], [15]. Most of the patients had Stage III COPD, and these patients had deteriorated clinically and were being treated in intensive care in the hospital.…”
Section: Discussionsupporting
confidence: 89%
“…Our study demonstrated that most of the COPD patients were heavy smokers, which are similar to results reported by other researchers in Adam Malik General Hospital (Medan) and M. Djamil Hospital (Padang), Indonesia [14], [15]. Most of the patients had Stage III COPD, and these patients had deteriorated clinically and were being treated in intensive care in the hospital.…”
Section: Discussionsupporting
confidence: 89%
“…Reflective use level has been had by 'climber' student in solving mathematics problem about PISA, they are able to understand, solve, and evaluate the problems [42]. They use their awareness and thinking ability in planning, observing, and evaluating the results of cognitive activities, so they get knowledge in solving the problems [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Tanaman mengambil air dan nutrisi dari media pertumbuhan melalui akar (Adams et al, 1995). Menurut Arifin dan Arifin (2002) sebagian besar unsur-unsur hara yang dibutuhkan tanaman dipasok melalui media tanam yang selanjutnya diserap oleh perakaran dan digunakan untuk proses fisiologi tanaman. Media tanam yang baik antara lain yang bersifat dapat menyerap air secara baik, cukup memiliki ruang yang porous, sehingga pada saat tanah basah diharapkan oksigen masih cukup diperoleh melalui perakaran.…”
Section: Hasil Dan Pembahasanunclassified